Enhancement of the cervical cancer screening program in malaysia: a qualitative study. - Abdullah, Fauziah; Tin, Tin Su (West Asia Organization for Cancer Prevention, 2010)
Introduction: Cervical cancer has long been known as a preventable disease. Yet it still is a prime women's health issue globally. In Malaysia, the current cervical cancer screening program, introduced in the 1960s, has been found to be unsuccessful in terms of Pap smear coverage. The aim of this study is to determine providers perceptives on the program and the feasibility of practicing an organized cervical screening program in Malaysia. Methods: 11 key informant interviews were conducted with policy makers and health care providers from the Ministry of Health in Malaysia from October 2009 to May 2010. Interviewees' perceptions were explored on current and organized cervical screening program based on their expertise and experience. Results: The results highlighted that the existing cervical screening program in Malaysia faced flaws at all levels that failed to reduce cervical cancer morbidity and mortality. The identified weaknesses were poor acceptance by women, lack of commitment by health care providers, nature of the program, an improper follow-up system, limited resources and other competing needs. Complementarily, all interviewees perceived an organized cervical screening program as an alternative approach both feasible and acceptable by women and government to practice in Malaysia. Conclusion: Better screening coverage depends on an effective screening program that incorporates a behaviour-based strategy. A new program should be focused in the policy-making context to improve screening coverage and to effectively combat cervical cancer.